Human resource management and the influence on organizational resilience for a private company. Trujillo – 2024 - Fernandez Piedra, Luis Miguel (2024)
The research aimed to analyze human resource management and its influence on organizational resilience in a private company in Trujillo, 2024. Through a causal correlational design and a quantitative approach, validated questionnaires were applied to a sample of 50 employees from a private organization. The results indicated that human resource management has a significant influence on organizational resilience, explaining 96.7% of its variability (Nagelkerke R²). Specifically, a strong influence was found on adaptation capacity (96.7%) and planning (90.6%). The analysis also revealed a positive impact on organizational learning, explaining 74.5% of its variability. These findings led to the conclusion that strategic human resource management is crucial for strengthening resilience, positioning it as a key factor for the company's sustainability and competitiveness in the face of internal and external challenges.